Learning to pray : a guide for everyone - Martin, James, 1960- (HarperOne, an imprint of HarperCollinsPublishers, 2021)
Explains what prayer is, what to expect from praying, how to do it, and how it can transform lives when it becomes a regular practice, discussing different styles and traditions of prayer throughout Christian history and encouraging readers to experiment and discover which works best for them.